STUDYING HOW EXOGENOUS FACTORS INFLUENCE ON FORMATION LIFE DURATION - Козовий, Р. В.; Ковальчук, Л. Є.; Децик, О. З. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
With purpose research of exogenous factors influence on formation life duration did survey and direct asking of 486 centenarians and 297 people of comparison group of Ivano-Frankivsk region. Found, that the biggest chance to reach longevity have people, that lived in favorable environmental conditions or people, that have high level of xenobiotics detoxification enzymes. About socio-psychologically conditions, the most important to reach longevity revealed absence of stress situation, high education, presence of strong sleeping and favorite occupation (p<0.001). Reliable significance on formation livelong and active life had compliance of naturally biorhythms, restrict diet, physical activity, absence of professional hazard and bad habits.